Mechanical and Water Absorption Properties of Jute/Palm Leaf Fiber-Reinforced Recycled Polypropylene Hybrid Composites. (9th May 2022) - Gideon, Rotich; Atalie, Desalegn
Abstract : Hybrid composites have proven endless benefits to the research communities in terms of environmental friendliness, mechanical properties, and development of new material. The present work explores the tensile, flexural, impact strengths, and water absorption properties of jute and palm leaf fiber-reinforced hybrid composites. Five types of hybrid composites were fabricated by varying jute and palm leaf fiber percentage of J100:P0, J25:P75, J50:P50, J25:P75, and J0:P100% with a constant weight ratio of polypropylene matrix. The findings showed that jute-palm leaf fiber-reinforced composite had positive effect on tensile, flexural, and impact strength. Experimental results showed that the J25:P75% (jute and palm leaf fiber) exhibited the highest tensile strength of 62.2 MPa and flexural strength of 82.26 MPa due to the optimal interfacial properties between the fibers and matrix. The impact strength of composites increased as the proportion of palm leaf fiber increased. Water absorption increased with jute fiber content, reaching a maximum of 1.26% at composite J100:P0, with lower water absorption at J0:P100% composite due to the higher moisture content of jute fiber.